Late Maastrichtian-early Paleocene calcium carbonate (%CaCO3) data from ODP Site 208-1262, South Atlantic - James S K Barnet; Kate Littler; Dick Kroon; Melanie J Leng; Thomas Westerhold; Ursula Röhl; James C Zachos (PANGAEA, 2025)
Calcium carbonate percentage (% CaCO3) records from ODP Site 1262 (Walvis Ridge, South Atlantic) covering the late Maastrichtian to early Paleocene (65.6 to 67.1 Ma). These data were measured between 2004 and 2007 and compiled to assess the magnitude of calcium carbonate dissolution at ODP Site 1262 during the Late Maastrichtian warming event and K/Pg boundary interval.